IMPROVING STUDENT MATHEMATICS LEARNING OUTCOMES WITH THE LEARNING MODEL CYCLE 5E CLASS VII - Halidin, halidin -; Subawo, Made; Arbain, Arbain (Universitas Sembilanbelas November Kolaka, 2023)
This research is a Classroom Action Research which aims to find out whether The Learning Cycle 5e Model can improve mathematics learning outcomes. The subjects of this study were students of class VIIc MTS Al-Ikhlas Iwoimenda, totaling 34 students.Â Retrieval of data with test results and observation sheets. Observation sheet data and mathematics learning achievement tests were analyzed using descriptive statistics.The results achieved after implementing the action through The Learning Cycle 5e Model for two cycles, namely: a) the average score of learning outcomes in cycle I is 63.10 from an ideal score of 100 and is in the sufficient category. It increased in cycle II to 78.43 from an ideal score of 100 and was in the good category. b) There was an increase in the percentage of observations of student activity in the first cycle of the first meeting by 41.67%, the second meeting was 66.67%, and in the second cycle first meeting was 83.33%, the second meeting was 91.67%. From the results of research on these data it can be concluded that The Learning Cycle 5e Model on operational material and properties of integer operations can improve the mathematics learning outcomes of class VIIc MTS Al-Ikhlas Iwoimenda.